An Overview of Psoriasis Vulgaris - Nopriyati; Reza Mayasari (HM Publisher, 2018)
Psoriasis is a chronic inflammatory skin disease with a genetic basis, characterized by impaired growth and differentiation of the epidermis, multiple biochemical, immunological, and vascular disorders. The aetiology of psoriasis is not known with certainty, thought to be triggered by an immune response due to environmental factors such as trauma, infection, or drugs in individuals who are genetically at risk of psoriasis. The pathogenesis of psoriasis begins with an inflammatory immune response that promotes the release of dendritic cells, T cells, keratinocytes, neutrophils, and cytokines.